P3.123 Population growth and evolutionary history of HIV-1 B and F subtypes in the northeast brazil. (8th July 2017) - Lima, Kledoaldo Oliveira de; Leal, Élcio; Cavalcanti, Ana Maria Salustiano; Salustiano, Daniela Medeiros; Lacerda, Heloísa Ramos
Abstract : Introduction: Despite low prevalence in the world, the HIV-1 subtype F is expanding in the state of Pernambuco, Northeast - Brazil, being the most prevalent subtype after subtype B. Increase of the frequency of other recombinants BF in the region, denoting the high capacity of recombination of subtype F with B. Thus, the objective of this work was to characterise the transmission dynamics between subtypes B and F in the state of Pernambuco, Northeast - Brazil. Methods: One hundred and fifty-six sequences of HIV-1 infected individuals were obtained from five Voluntary and Counselling Testing Centres (VCTs) in the state of Pernambuco (Northeast - Brazil), of which 103 were HIV-1 B and 53, HIV-1 F. Samples were collected between 2002 and 2009. We used the Bayesian Markov chain Monte Carlo (BMCMC) coalescent framework to estimate the ancestral genealogy, phylodynamics and evolutionary parameters such as nucleotide substitution rates per year and time to the most common ancestor (tMRCA) with BEAST package version 1.8.1. Results: Pattern of population growth are similar between subtype B in Brazil and in Pernambuco showing a pattern of steep exponential growth followed by a plateau in the diversity. Population dynamics of subtype F shows a moderate growth phase continuously expanding and the beginning of infection started later than that of global subtype F infection. The coalescent method also provided the date of introduction of HIV-1 in Pernambuco since the inferred time to the most recent common ancestral (tMRCA) was 1978 (95% CI: 1971–1981) and 1982 (95% CI: 1977–1986) respectively for the subtypes B and F. Conclusion: Introduction of subtype B occurred earlier in other regions of Brazil than in Pernambuco (Northeast, Brazil). Subtype F is in population expansion around the world and in Brazil. In addition, introduction of subtype F in Pernambuco (Northeast) was later than in the country (1982, CI95%: 1977–1986). These findings support the hypothesis that the viral variability of HIV-1 is increasing in Brazil with the spread of subtypes non-B.